O projeto estético de Graciliano Ramos: por uma literatura sem adjetivos - Borges, Lilliân Alves (2021)
Graciliano Ramos holds a place within the Brazilian literary canon. He is known for adult narratives: Barren Lives, by University of Texas Press, translated by Ralph Edward Dimmick; Childhood, by London publisher Peter Owen, translated by Celso Lemos de Oliveira; Anguish, by University of California, translated by Lewis C. Kaplan; Memórias do cárcere (Memoirs of prision); which are widely read and study for general public and literary critics. In contrast to extensively adults narratives studies, children narratives are let in critical silence, such as A terra dos meninos pelados (The land of naked boys), Histórias de Alexandre (Histories of Alexandre) and Pequena História da República (Little History of the Republic). Beside adult and children narratives, “Luciana” and “Minsk” are tales published in the book Insônia. Therefore, reflecting about critical silencing and some that try to discredit Graciliano Ramos children narratives, thesis aims to demonstrate Ramos had coherent and cohesive aesthetic project presented to readers and aesthetic harmony in adults and children works. Reflections about children's literature are propelled by Childhood, since analysis will based in the narrative and compared to Brazilian children's literature history, highlighting Graciliano Ramos school literature and children's literature understanding by literary traces in his narratives. Theoretical framework about children's literature is based on Marisa Lajolo, Regina Zilberman, Ligia Cademartori Magalhães, Maria Antonieta Antunes Cunha, Jesualdo Sosa, Marisa Martins Gama-Khalil and Peter Hunt studies among others. Then, all Graciliano Ramos' children narratives will be analyzed, because no systematic study in this thematic was carried yet, and, therewith, unveil aesthetic potential of each Ramos narratives. Space theoretical notions issue from Gaston Bachelard, Yi-Fu Tuan and Michel Foucault studies. Fantastic literature theories proposed by Remo Ceserani, Filipe Furtado, Lenira Marques Covizzi, Gama-Khalil, in addition to Michel Foucault's subjectivation and (un)subjectivation notions support analisys. Finally, in the last chapter, we will make a brief journey on Graciliano Ramos some narratives directed to adults, showing contact and distancing points with children narratives, thus proving our initial hypothesis that Ramos when writing books for children and adults presents the same literary principles in the texts for both audiences. There is, therefore, a coherence in aesthetic project making, which is marked significantly by ethical and aesthetic action.